Embedding Co2P nanoparticles into co-doped carbon hollow polyhedron as a bifunctional electrocatalyst for efficient overall water splitting. (24th June 2020) - Li, Yan; Cui, Mengnan; Li, Tianjiao; Shen, Yu; Si, Zhenjun; Wang, Heng-guo
Abstract: The reasonable design and construction of non-precious metal electrocatalysts with low cost and high performance is critical for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Herein, a facile polymerization-pyrolysis method is proposed to encapsulate Co2 P nanoparticles in co-doped hollow carbon shell by using ZIF-67 and P-containing polymers as precursor. The unique construction not only effectively prevents nanoparticles from detaching, showing good stability after long-term testing, but also provides abundant active sites, large surface areas and large pore volumes, enabling the electrolyte and electrode material to full contact. As expected, the Co2 P/NPSC-800 performs superior HER performance with low overpotential of 173 mV at 10 mA cm −2 and excellent stability of 88% retention for 35 h and OER performance with low overpotential of 320 mV at 10 mA cm −2, which endows Co2 P/NPSC-800 with good catalytic activity in overall water splitting. Furthermore, density functional theory (DFT) calculations reveal that the metallic property and the decreased reaction barriers of Co2 P can promote the catalytic reactions. This work offers an effective route in synthesizing other transition metal phosphides with high catalytic properties. Graphical abstract: Image 1 Highlights: Co2 P nanoparticles were embedded in co-doped hollow carbon shell by a facile method. The composite was prepared by pyrolyzing the polymer coated metal-organic frameworks. The samples can be served as a bifunctional electrocatalyst for both HER and OER. Theoretical calculation show that the metallic property and the low reaction barrier.